The isolation of lutein and lutein 3′-methyl ether from peristrophe lanceolaria - Prapalert W. (2017)
Two carotenoids, lutein (1) and lutein 3′-methyl ether (2), have been isolated from the EtOAc fraction of the MeOH extract of Peristrophe lanceolaria, growing in Thailand. The structures of these compounds were elucidated from their 1D and 2D NMR spectroscopic data and from comparisons made with the literature data. This is the first report of the isolation of lutein-3′-methyl ether as a natural product.